2021
DOI: 10.3389/fmolb.2021.688973
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Impact of R-Methylation on RBPs-RNA Interactions: A Proteomic Approach

Abstract: RNA binding proteins (RBPs) bind RNAs through specific RNA-binding domains, generating multi-molecular complexes known as ribonucleoproteins (RNPs). Various post-translational modifications (PTMs) have been described to regulate RBP structure, subcellular localization, and interactions with other proteins or RNAs. Recent proteome-wide experiments showed that RBPs are the most representative group within the class of arginine (R)-methylated proteins. Moreover, emerging evidence suggests that this modification p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…4 C ). This observation was corroborated by a very recent study published by our group showing that R methylation is involved in the assembly of membrane-less organelles through the modulation of RBP–RNA interaction ( 17 ).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…4 C ). This observation was corroborated by a very recent study published by our group showing that R methylation is involved in the assembly of membrane-less organelles through the modulation of RBP–RNA interaction ( 17 ).…”
Section: Resultssupporting
confidence: 71%
“…While methylation of histones and its implication in transcriptional regulation has been extensively studied in several model systems and functional states ( 6 ), the concept that R methylation is widespread on non-histone proteins is supported by more recent studies ( 7 , 8 , 9 , 10 , 11 ). PRMT1, PRMT3, PRMT4, PRMT5, and PRMT7 have all been reported to catalyze methylation on RNA-binding proteins (RBPs), modulating their interactions with RNAs and thus impacting on biological processes, such as mRNA splicing, miRNA maturation, translation, and ribonucleoprotein (RNP) granules assembly ( 8 , 12 , 13 , 14 , 15 , 16 , 17 ). Importantly, PRMTs are often aberrantly expressed in cancer ( 18 , 19 ) and in neurodegenerative and metabolic disorders ( 20 , 21 ).…”
mentioning
confidence: 99%
“…This region is on the border of the DBD and the hinge domain, and R260 is within this region. RBPs are a main group of arginine-methylated proteins, and the arginine methylation of RBPs affects RBP-RNA interactions [ 86 ]. Although it is unclear how the methylation status of the ERα R260 (and R264 in mouse ERα) influences ERα’s function as an RBP, the substitution of four amino acids including R260 to unmethylated alanine disrupts the ERα’s RBP function, leading to changes in an alternative splicing and translation of the target genes without affecting the DNA-binding ability [ 85 ].…”
Section: Erα Isoform Variation and Functionsmentioning
confidence: 99%
“…Indeed, even if previous studies from her group have demonstrated that cisplatin treatment could change PRMT subcellular localization, her results suggest a novel layer of complexity. In response to the cisplatin treatment the R-hypomethylation on RBPs, the consequent modulation of RBP-RNA binding and their subcellular localization can occur ( Maniaci et al, 2021 ).…”
Section: Rna Structure Localization and Rna–protein Interactionmentioning
confidence: 99%